A binomial expression is one that has two terms, such as 3a - 1

When we add and subtract binomials, we combine the letter terms and the numbers separately.

Be careful with - signs and try to put the letter term first

(i.e. 3a -1 rather than -1 + 3a).

**Example 1**

Simplify

(3a - 1) + (2a + 7)

**Answer**

(3a - 1) + (2a + 7)

= 3a - 1 + 2a + 7

= 3a + 2a - 1 + 7

= **5a + 6**

**Example 2**

Simplify

(3a - 1) - (2a + 7)

**Answer**

(3a - 1) - (2a + 7)

= 3a - 1 - 2a - 7

= 3a - 2a - 1 - 7

=** a - 8**

**Example 3**

Simplify

(3a - 1) - (2a - 7)

**Answer**

(3a - 1) - (2a - 7)

= 3a - 1 - 2a + 7

= 3a - 2a - 1 + 7

= **a + 6**